Potential side effects of antibacterial coatings in orthopaedic implants: A systematic review of clinical studies - Li, Hua; Wang, Daofeng; Zhang, Wupeng; Xu, Gaoxiang; Xu, Cheng; Liu, Wanheng; Li, Jiantao (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: The systematic review aimed to determine the potential side effects of antibacterial coatings in orthopaedic implants. Methods: Publications were searched in the databases of Embase, PubMed, Web of Science and Cochrane Library using predetermined keywords up to 31 October 2022. Clinical studies reporting side effects of the surface or coating materials were included. Results: A total of 23 studies (20 cohort studies and three case reports) reporting the concerns about the side effects of antibacterial coatings were identified. Three types of coating materials, silver, iodine and gentamicin were included. All of studies raised the concerns regarding safety of antibacterial coatings, and the occurrence of adverse events was observed in seven studies. The main side effect of silver coatings was the development of argyria. For iodine coatings, only one anaphylactic case was reported as an adverse event. No systemic or other general side effects were reported for gentamicin. Conclusion: Clinical studies on the side effects of antibacterial coatings were limited. Based on the available outcomes, the most reported side effects of antibacterial coatings in clinical use were argyria with silver coatings. However, researchers should always pay attention to the potential side effects of antibacterial materials, such as systematic or local toxicity and allergy.